The Application of Informatics Logic in The Importation of Goods From Outside to Indonesia - Dian Damayanti; Muhammad Ridho; Zaki Zain; Jailani Arsad; Fanny Ramadhani (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
Logic is a method or technique that was created to examine the accuracy of reasoning and study the principles of correct reasoning and conclusion. Logic is also called "the calculus of computer science" because logic plays an important role in the field of computer science. Not only that, the role of calculus. (mathematics) is equally important for the sciences in the fields of science, economics and also in everyday life. In this study is to provide rules for making decisions on the problem of the number of imported goods entering Indonesia. The method used by the author to complete the research This is using the truth table of the problems to be solved, calculus of propositions, problems to be solved, Studying things from research in general and various methods of solving, the writer also looks for written sources. The definition of a proposition or statement is a declarative sentence that has exactly one truth value. namely: "True" (T) or u "False" (F). Proposition calculus is a method for calculating using propositions / sentences. In proposition calculus reviewed is the value of a declarative sentence (TRUE / FALSE). Logical operations contain a collection of operations that include negation, conjunction disjunction, implication, and bi implication.